Legal and Social Implications of Underage Marriage in the Context of Islam and Legislation - Ekaningsih, Lely Ana Ferawati (STAI Miftahul Ula Nganjuk, 2024)
Marriage is a social institution that aims to form a harmonious and prosperous family. However, in several regions in Indonesia, the practice of underage marriage is still rampant even though there are regulations governing the minimum age of marriage, such as in Marriage Law No. 1 of 1974. This study aims to examine the factors behind the practice of underage marriage, its implications for domestic life, and how Islamic law and Indonesian positive law view this phenomenon. The results show that economic factors, culture, promiscuity, and lack of understanding of the law are the main causes of underage marriage. This practice often has a negative impact on children's health, education and welfare, and increases the risk of divorce. Therefore, it is necessary to strengthen regulations, increase public awareness, and interventions from various parties to reduce the number of underage marriages.